THE STUDENTS’ PERCEPTION TOWARD THE IMPLEMENTATION OF PEER FEEDBACK RECEIVER IN DEBATE SUBJECT - Muthia Mutmainnah Darmuh; Erwin Akib (University of Muhammadiyah Purwokerto, 2017)
This study aimed to find out the students’ perception as the spoken feedback receiver towards the implementation of peer feedback in Debate subject. The data collection was conducted from June to August 2016. The data was collected from 15 students of English Education Department year 2013 from 6 classes of Debate Subject. This study used qualitative research design in collecting data. The instrument which was used to collect the data was questionnaire. The questionnaire was distributed to 15 students of English Education Department from year 2013. The items of the questionnaire were open ended questions as qualitative questionnaire. Based on the findings, it finds that students gave the positive perception towards the implementation of peer feedback in Debate subject class either as spoken feedback receiver. Moreover, the students claimed that they have got many advantages during the implementation of peer feedback. This study also found out that this strategy was needed to be improved by the lecturers in terms of giving instruction, observing the class and evaluating the feedback from the students. DOWNLOAD ABSTRACT